Intoleransi Antar Umat Beragama Di Media Sosial (Studi Pada Youtube Deddy Corbuzier Program Log In – Eps 30 “Toleransi, Kita Cetak Sejarah) - Childa Tanzilul Hidayah; Kun Kun Kurniawan (Hikmah, 2025)
This study examines the representation of interfaith communication in social media content through an analysis of the Log In program episode 30 entitled "Tolerance, We Print History". As one of the contents that discusses the issue of religious tolerance on digital platforms, this episode is an important object of study to understand how dialogue and interaction between religious communities are constructed and conveyed through social media. Using a qualitative content analysis method, this study aims to identify communication patterns, narratives, and tolerance values built in the episode. The analysis was carried out by paying attention to three main aspects: (1) the way to convey the message of interfaith tolerance, (2) the representation of interfaith dialogue, and (3) the framing strategy of sensitive issues related to religion. The results of the study show that Log In episode 30 succeeded in building a narrative of tolerance through a storytelling approach that presents real stories about harmony between religious communities. This program is also effective in presenting constructive dialogue involving perspectives from various religions, while maintaining the sensitivity of religious issues. Other important findings are the use of inclusive language and visuals, as well as messaging strategies that prioritize universal human values. This research contributes to the understanding of how social media content can play a role in building positive interfaith communication and supporting the creation of religious tolerance in the digital era.